MAHALLA – AN IMPORTANT INSTITUTE OF CIVIL SOCIETY - Urakova Nargiza Salomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The land of society is an important element of civil society. It denotes the independence and initiative of various spheres of public life and related associations: economy, that is, production in a broad sense, its organizational forms, trade unions, universities, the Press, science, public associations, mosques, religious organizations, etc. With regard to these public associations, the task of the state should be to establish the most common boundaries in the form of a law regulating the rules of the game, which must be observed in order to protect the rights and freedoms of all members of the society. Of course, in our country, the neighborhood is one of the pillars that make up the basis of this society. In this article, comments are made on the fact that the neighborhood is an important institution of civil society.